FAKTOR YANG MEMPENGARUHI KUALITAS HIDUP PASIEN SKIZOFRENIA : LITERATUR REVIEW - Tunjung Sri Yulianti (KOSALA : Jurnal Ilmu Kesehatan, 2021)
Latar Belakang: skizofrenia merupakan suatu hal yang melibatkan banyak sekali faktor. Faktor tersebut adalah perubahan struktur fisik otak, perubahan struktur kimia otak dan faktor genetik. Skizofrenia merupakan penyakit neurologis yang mempengaruhi persepsi klien, cara berfikir, bahasa, emosi, dan perilaku sosialnya.Terdapat beberapa faktor yang dapat mempengaruhi kualitas hidup pasien skizofrenia. Karena itu, mengetahui faktor kualitas hidup pasien skizofrenia sangat penting dimana dapat dijadikan acuan untuk mengidentifikasi kualitas hidup pasien skizofrenia dan faktor yang mempengaruhinya. Tujuan penelitian: untuk mengetahui faktor yang mempengaruhi kualitas hidup pasien skizofrenia. Metode: desain penulisan adalah literatur review. Populasi diambil dari seluruh jurnal penelitian dengan topik kualitas hidup pasien skizofrenia. Sampel pada penelitian ini adalah 5 jurnal tentang kualitas hidup pasien skizofrenia yang memenuhi kriteria inklusi. Hasil: hal-hal yang terkait dengan kualitas hidup pasien skizofrenia yaitu kesehatan fisik, kesehatan psikologis, hubungan sosial, lingkungan kesehatan dan sosial, fungsi sosial, kepatuhan minum obat dan kepatuhan berobat. Kesimpulan: faktor yang mempengaruhi kualitas hidup pasien skizofrenia mencakup fungsi keluarga dan dukungan keluarga, stigma diri, harga diri, daya tilik diri. Kata kunci: skizofrenia, kualitas Hidup FACTORS AFFECTING THE QUALITY OF LIFE OF SCHIZOPHRENIC PATIENTS : LITERATURE REVIEW Tunjung Sri Yulianti Abstract Background: schizophrenia is a multi-factor issue. These factors are changes in the physical structure of the brain, changes in the chemical structure of the brain and genetic factors. Schizophrenia is a neurological disease that affects the client's perception, way of thinking, language, emotions, and social behavior.There are several factors that can affect the quality of life of schizophrenic patients. Therefore, knowing the quality of life factors of schizophrenia patients is very important which can be used as a reference. So this study was conducted to find appropriate prevention efforts so that the quality of life of schizophrenia patients was not low. The aim of the study: to determine the factors that affect the quality of life of schizophrenic patients. Method: the writing design is a literature review. Literature review is the process of research or writing scientific papers, where literature is used as a data source. The population was taken from all journals of quality of life for schizophrenia patients. The samples in this scientific paper were 5 journals of quality of life for schizophrenia patients that met the inclusion criteria. Result: things related to the quality of life of schizophrenic patients, namely physical health includes: daily life activities, dependence on drugs and medical assistance, psychological health includes: body image and appearance, negative feelings, feelings of spirituality / religion / personal beliefs, thinking, relationships. social includes: personal relationships, social support and sexual activity. Environment includes: financial resources, freedom, physical security, health and social services: affordability and quality, home environment. Conclusion: factors that affect the quality of life of schizophrenic patients include physical health, psychological health, social and environmental relationships Keywords: schizophrenia, quality of life.